KONSEP SAHABAT MENURUT MAá¸¤FÅªáº’ AL-TARMASÄª (1842-1920 M) - Anshori, Muhammad (IAIN Kediri, 2017)
This article tries to explore the concept of shahabat in a book Manhaj Ã…Â»awÃ„Â«al-NaÃ¡Âºâ€œar written by MaÃ¡Â¸Â¥fÃ…Â«Ã¡Âºâ€œ al- TarmasÃ„Â«. This book is SharÃ¡Â¸Â¥ NaÃ¡Âºâ€œm AlfÃ„Â«yah al-SuyÃ…Â«Ã¡Â¹ÂÃ„Â« (died in 911 H) consisting of 980 stanzas, and is added 20 stanzas by al-TarmasÃ„Â«, so the total is 1000 stanzas. One of the interesting point to be discussed in hadith study is the concept of shahabat, the first source of hadith. The validity of shahabat becomes polemic between Sunni and ShiÃ¢â‚¬â„¢i, especially on the concept of shahabat justice. In the book, there is no new concept of shahabatÃ¢â‚¬â„¢s justice in general. Al- TarmasÃ„Â« only repeats the previous ulamaÃ¢â‚¬â„¢s explanations in his book. By following the majority of ulama, he states that all shahabat are Ã„Âdil (fair), but the reality shows that not all of them are Ã„Âdil (fair). This article has been proved it by quoting some sources. Modern Muslim scholars also ask about the concept of al-Ã¡Â¹Â£aÃ¡Â¸Â¥Ã„Âbah kulluhum udÃ…Â«l. In some literatures, it has been mentioned some shahabatÃ¢â‚¬â„¢s attitudes that did not show the Islamic values. There are many examples of bad shahabatÃ¢â‚¬â„¢s behavior, so it can be said that the concept of al-Ã¡Â¹Â£aÃ¡Â¸Â¥Ã„Âbah kulluhum udÃ…Â«l does not have to be understood that all shahabat are Ã„Âdil (fair). The appropriate meaning is that some of shahabat are Ã„Âdil (fair) since Ã¢â‚¬Å“kulluÃ¢â‚¬Â here is juzÃ¢â‚¬â„¢iyah (some), not kulliyah (whole). Keywords: Ã„Âdil, MaÃ¡Â¸Â¥fÃ…Â«Ã¡Âºâ€œ al-TarmasÃ„Â«, Manhaj Ã…Â»awÃ„Â«al-NaÃ¡Âºâ€œar, Sahabat